2012
DOI: 10.1111/j.1524-475x.2012.00779.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of attitudes toward the source of progenitor cells in tissue‐engineered products for use in burns compared with other disease states

Abstract: The first trials using progenitor cells to improve burn wound healing are beginning. However, there remains a paucity of data on patients' opinions of the source of stem cells. In this study, 279 patients attending plastic surgery/burns outpatient and medical outpatient clinics were questioned to assess willingness to accept a tissue-engineered skin product derived from a variety of sources. Levels of acceptance for the use of progenitor cells derived from these sources for treatment across a range of disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…People are now more educated about the different sources of stem cells and have become supportive of their use [ 85 ]. Regarding the acceptance of stem cells as an efficient therapy for burn wound healing in specific, a study done by Clover et al [ 86 ] showed a very positive opinion. The biggest majority of people were willing to accept autologous stem cells, though a big percentage was also welcoming the idea of using allogeneic stem cells.…”
Section: Reflections On the Role Of Stem Cells In Burn Wound Healimentioning
confidence: 99%
See 1 more Smart Citation
“…People are now more educated about the different sources of stem cells and have become supportive of their use [ 85 ]. Regarding the acceptance of stem cells as an efficient therapy for burn wound healing in specific, a study done by Clover et al [ 86 ] showed a very positive opinion. The biggest majority of people were willing to accept autologous stem cells, though a big percentage was also welcoming the idea of using allogeneic stem cells.…”
Section: Reflections On the Role Of Stem Cells In Burn Wound Healimentioning
confidence: 99%
“…The biggest majority of people were willing to accept autologous stem cells, though a big percentage was also welcoming the idea of using allogeneic stem cells. These percentages did not differ between the use of stem cells for burn wounds or for the treatment of other diseases such as diabetes or Parkinson's [ 86 ].…”
Section: Reflections On the Role Of Stem Cells In Burn Wound Healimentioning
confidence: 99%
“…In other studies with different patient groups such as patients with Parkinson's disease, many patients displayed misconstrued knowledge or were unaware of SCT [9]. Moreover, autologous stem cells seem to be preferred to allogeneic cells by patients with burn injuries, Parkinson's disease, and diabetes mellitus, as reported in a study on attitudes to progenitor cell source [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some may hold views on the use of embryonic stem cells or fetal cells, or pig xenogeneic tissue; some may prefer autologous cells, where possible, to donor cells. It has been demonstrated in a questionnaire-based study, for instance, that autologous cells were the preferred choice of cell for patients suffering from various diseases, including Parkinson’s [ 15 ]. This study showed that “patients have a hierarchy of preferred source of cells for use in tissue-engineered products” and that attitudes toward stem cell therapy “may be influenced by the patient’s disease state”.…”
Section: Helping Patients To Make An Informed Choice: Steps To Considmentioning
confidence: 99%